A case study for cuts in soft soils - Köseli, M. Erhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1992., 1992)
The slope stability problems resulting from soft subsoil conditions on the unbraced excavated cuts are usually observed as rapid and sudden landslides. This is even more evident in the case of inappropriate slope application on this kind of soil conditions. The approaches for the remedial solutions of such problems generally concentrate on the regrading of the inappropriate material and flattening the applied slopes. However, in such cases, it is more important to identify the subsoil conditions properly and to perform the detailed analyses accordingly. In this respect, the landslide which had occurred at TAG motorway during the excavation of cut slopes between Km.141+400 and Km.141 + 700 is investigated as a case study. The required analyses are performed in order to determine the residual strength parameters by both laboratory tests and back calculation method. In the light of these analyses, it is determined that the real cause to slip is the inadequate slope application on the soft soil conditions. During the analyses, it is also observed that there is a logical relationship between soil properties and residual strength parameters which can give profitable data for designers where the remedial solutions are urgent. The residual internal friction angle of slipped soil is obtained as 14 degree.
Keywords: Slopes (Soil mechanics); Soil mechanics.